2015
DOI: 10.2174/1566524015666150330144018
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Learning and Increase in Dopamine Level in the Frontal Cortex by Methylphenidate in Mice Lacking Dopamine Transporter

Abstract: The symptoms of attention-deficit/hyperactivity disorder (ADHD) are characterized by inattention and hyperactivity-impulsivity. It is a common childhood neurodevelopmental disorder that often persists into adulthood. Improvements in ADHD symptoms using psychostimulants have been recognized as a paradoxical calming effect. The psychostimulant methylphenidate (MPH) is currently used as the first-line medication for the management of ADHD. Recent studies have drawn attention to altered dopamine-mediated neurotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
8
0
3
Order By: Relevance
“…Although the neuropathology of the brain was corrected in only some regions, we were able to achieve correction of hyperactive behaviour and working memory in AAV-TT treated mice over AAV9 treated mice. It is unclear which brain area is responsible for hyperactivity in MPS, however, the frontostriatal pathway has been implicated in ADHD ( Cubillo et al , 2012 ), as it is involved in control of impulsivity, locomotion, affect, attention and emotion ( Takamatsu et al , 2015 ). This pathway connects the cortex, striatum and thalamus ( Morris et al , 2016 ), areas in which we have observed improvement in LAMP2, GFAP and ILB4 levels with AAV-TT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the neuropathology of the brain was corrected in only some regions, we were able to achieve correction of hyperactive behaviour and working memory in AAV-TT treated mice over AAV9 treated mice. It is unclear which brain area is responsible for hyperactivity in MPS, however, the frontostriatal pathway has been implicated in ADHD ( Cubillo et al , 2012 ), as it is involved in control of impulsivity, locomotion, affect, attention and emotion ( Takamatsu et al , 2015 ). This pathway connects the cortex, striatum and thalamus ( Morris et al , 2016 ), areas in which we have observed improvement in LAMP2, GFAP and ILB4 levels with AAV-TT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In DAT-KO mice it showed its ability to reduce spontaneous hyperactivity (Gainetdinov et al, 1999b) and increase the extracellular level of DA in the prefrontal cortex, but not in the striatum (Takamatsu et al, 2015). Rewarding properties of MPH are also preserved in DAT-KO mice in conditional place preference test (Sora et al, 1998).…”
Section: Dat Knockout (Dat-ko) Micementioning
confidence: 99%
“…In the water maze, following haloperidol administration, DAT-KOs became as successful as WT mice in finding the platform, and their performance markedly improved with training (Morice et al, 2007). Finally, DAT-KO mice showed impairment of avoidance behavior in shuttle box, which could be reversed by methylphenidate (Takamatsu et al, 2015). …”
Section: Dat Knockout (Dat-ko) Micementioning
confidence: 99%
“…The blockade of dopaminergic neurotransmission with dopamine receptor antagonists also results in motor impairment [ 8 ]. In contrast, dopamine transporter knockout mice, which have high levels of dopamine, exhibit hyperactivity [ 9 ]. Based on these observations, dopamine concentrations may be correlated with the extent of locomotor activity.…”
Section: Introductionmentioning
confidence: 99%